1982
DOI: 10.1902/jop.1982.53.5.315
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hypertonic Saline and Chlorhexidine Mouthrinses After the Inverse Bevel Flap Procedure

Abstract: THE VALUE OF periodontal dressings after periodontal surgery has been questioned. This study further evaluated chlorhexidine as a possible alternative. A group of nine patients requiring comparable bilateral inverse bevel flap procedures underwent preoperative oral hygiene instruction and scaling. Immediately before surgery and up to 3 months postoperatively, clinical records of plaque index, pocket depths and sulcus bleeding index were made. Records were taken of patients' postoperative discomfort and prefere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Studies with split mouth design have been used to compare healing of surgical sites with or without a periodontal dressing, Stahl et al, (1969) found that the use of a dressing makes little difference to healing following gingivectomy procedures, similarly no healing advantage was demonstrated when a pack was used following reverse bevel flap surgery (Greensmith & Wade 1974, Jones & Cassingham 1979 or modifled Widman flap procedures (Allen & Caffesse 1983). In contrast, Newman & Addy (1982) found advantage in using a 0.2".A, chlorhexidine rinse when compared with a periodontal dressing and saline rinse following inverse bevel flap procedures. At 1 week post operation, both plaque accutnulation and sulcus bleeding were significantly lower with a chlorhexidine mouth rinse, but at the I month examination, no significant differences were found between treatments.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Studies with split mouth design have been used to compare healing of surgical sites with or without a periodontal dressing, Stahl et al, (1969) found that the use of a dressing makes little difference to healing following gingivectomy procedures, similarly no healing advantage was demonstrated when a pack was used following reverse bevel flap surgery (Greensmith & Wade 1974, Jones & Cassingham 1979 or modifled Widman flap procedures (Allen & Caffesse 1983). In contrast, Newman & Addy (1982) found advantage in using a 0.2".A, chlorhexidine rinse when compared with a periodontal dressing and saline rinse following inverse bevel flap procedures. At 1 week post operation, both plaque accutnulation and sulcus bleeding were significantly lower with a chlorhexidine mouth rinse, but at the I month examination, no significant differences were found between treatments.…”
mentioning
confidence: 78%
“…Reports of patient preference for the use of a dressing are also controversial. A greater number of patients preferred the use of chlorhexidine rinse alone following inverse bevel flap procedures (Newman & Addy 1982), whilst preference was expressed for the use of a dressing following gingivectomy (Addy & Dolby 1976) and apically positioned flap surgery (Checchi & Trombelli 1993). in the latter study, most patients reported a psychological feeling of protection and well being when a dressing was placed after surgery…”
mentioning
confidence: 90%
“…These results are in accordance with the study of Heaney and Appleton[14] (1976), Pluss et al . (1975),[15] Newman and Addy (1982),[16] Sachs et al . (1984)[17] who reported accumulation of plaque beneath the periodontal dressings but not to a detrimental level to retard the healing process.…”
Section: Discussionmentioning
confidence: 99%
“…Results from a number of questionnaire studies, however, do not appear to suggest that patients stop brushing their teeth if they experience discomfort from DH/RDS (5,(30)(31)(32)(33). Indeed, there is evidence to suggest that plaque is not a major etiological factor as DH/RDS can occur postsurgery irrespective of any instituted oral hygiene standards (80). Indeed, there is evidence to suggest that plaque is not a major etiological factor as DH/RDS can occur postsurgery irrespective of any instituted oral hygiene standards (80).…”
Section: Role Of Oral Hygienementioning
confidence: 99%